Arctic Challenge for Sustainability (ArCS) project - Fukasawa, Masao (Polar Science, 2021)
A national Arctic research project of “Japan's national project of Arctic Challenge for Sustainability (ArCS)” finished in March 2020. A special issue for ArCS was prepared to summarize performances of ArCS through fourteen invited articles that were reviewed activities and achievements of ArCS. In this Editorial, major facts and the structure of ArCS are shown. Also, each invited article is introduced briefly with its individual characteristics within the whole ArCS research system. journal article